Lost in transition : constructing memory in contemporary Spain - Song, H. Rosi, 1970- (Contemporary Hispanic and Lusophone cultures., 2016)
This book examines contemporary recollection of Spain's transition to democracy in the late 1970s and its connection to the country's current political, financial and cultural crises through fiction, film, and television.